Hannibal : Hannibal rising - Webber, G. P. (G. Peter); Ben Ammar, Tarek; De Laurentiis, Dino; De Laurentiis, Martha; Harris, Thomas, 1940-; Ulliel, Gaspard, 1984-; Gong, Li, 1965-; West, Dominic, 1969-; Tachovska, Helena Lia; Ifans, Rhys, 1967-; Brake, Richard; McKidd, Kevin; et al. (New York, N.Y Weinstein Company, 2007)
After young Hannibal is forced to watch his little sister, Mischa, being devoured by starving soldiers in his Lithuania homeland. Hannibal vows to avenge his sister's death by slaying those who committed not only war crimes against the Lecters, but also against other families during WW II. Hannibal's revenge plan includes his cannibalism to justify his insatiable appetite for human flesh. Hannibal excels in his medical school classes dissecting cadavers. Complications arise when Hannibal interacts with his sexy Aunt, Lady Murasaki. Murasaki educates him in the art of beheading and Hannibal learns too that his sword fetish is a manifestation of physical lust.
Based on the novel by Thomas Harris.
Special features: commentary by director and producer Martha De Laurentiis; deleted scenes with optional commentary; Hannibal Lecter, the origin of evil; Allan Starski, designing horror and elegance; trailers.
Director of photography, Ben Davis ; editors, Valerio Bonelli, Pietro Scalia ; music, Ilan Eshkeri, Shigeru Umebayashi ; costume designer, Anna Sheppard ; production designer, Allan Starski.
Gaspard Ulliel, Li Gong, Dominic West, Helena Lia Tachovska, Rhys Ifans, Richard Brake, Kevin McKidd, Stephen Walters, Ivan Marevich, Aaron Thomas.
Unrated; for strong grisly violent content and some language/sexual references.
DVD, region 1, widescreen presentation; Dolby Digital 5.1.
Keywords: Lecter, Hannibal -- (Fictitious character), -- 1933- -- Drama; World War, 1939-1945 -- Atrocities -- Lithuania -- Drama; Murder -- France -- Drama; Medical students -- France -- Drama; Dissection -- Drama; Atrocities; Homicide -- France -- Drama; France; Lithuania; Thrillers (Motion pictures, television, etc.); DVD-Video discs; Drama; Feature films; Horror films; Suspense films